Stensil Sebagai Media Aspirasi Dalam Wacana Desain Komunikasi Visual - Antonius Purwantono (DeKaVe, 2012)
Stencil is one of street art forms such as mural and graffity. It's simplicity and thepeople/community perceptions towards the street art have made stencil as a medium for street art artist toexpress their ideas. Today, stencil becomes the form of street art practices and is used as visual designelements wich can be applied as profitable commodity